THE EFFECTIVE WAYS OF TEACHING SPEAKING TO YOUNG LEARNERS USING IDIOMS - Sidikova.N.N,; Isroilova Zulfiya Sirojiddinovna,; Karomiddinova Sitorabonu Kamoliddin qizi, (TADQIQOTLAR, 2026)
This article explores effective strategies for teaching speaking skills to young learners  through  the  use  of  idioms.  It  emphasizes  the  significance  of  idioms  in enhancing language fluency and cultural understanding. The article outlines various pedagogical  approaches,  including  contextual  learning,  visual  aids,  role-playing activities, and interactive games, to engage students and facilitate their understanding of  idiomatic  expressions.  Furthermore,  it  discusses  assessment  methods  to  track progress  and  encourage  the  continued  use  of  idioms  in  everyday  conversation.  By integrating idioms into language instruction, educators can foster a more authentic and expressive use of language among young learners.